Antibiotic resistance of enterococci isolated from frozen foods and environmental water - Unchalee Tansuphasiri (2018)
We evaluated 239 isolates of enterococci (113 from frozen foods and 126 from environmental water) for their resistance to 8 antibiotics by agar disk diffusion method. Most isolates from both sources were resistant to tetracycline (64.1 % food strains; 46.8% water strains) and ciprofloxacin (53.4% food strains; 48.4% water strains). A relatively high prevalence of chloramphenicol, trimethoprim-sulfamethoxazole and vancomycin resistance was present, ranging from 9.7 to 27.2% for food strains and 10.3 to 15.9% for water strains; while other drug resistance (ampicillin, gentamicin and teicoplanin) was minimal (≤0.9% for food strains; ≤1.6% for water strains). No significant differences in resistant rates between the two sources were found for any of the drugs (p>0.05) except tetracycline (p<0.05). The majority of isolates from both sources were multi-resistant strains (50% for food strains and 42% for water strains). Most of them showed resistance to two drugs. There was no significant difference in the non-resistance patterns and the multidrug resistance patterns (p>0.05) between the frozen food and environmental water strains, but a significant difference was seen in the single drug resistance pattern (p<0.05). Vancomycin resistant enterococci (VRE) were isolated from nearly all sources studied, 9.7% food isolates and 10.3% water isolates, with no significant difference between the two sources (p>0.05). This study shows a high prevalence of multidrug resistance among enterococci isolated from foods of animal origin and environmental water. This may serve as a potential transfer route of antibiotic-resistant bacteria and resistant genes into the human food-chain and environment which could potentially pose a health threat to humans in the future. The use of antibiotics for purposes other than human health, ie in animal feeds and in the treatment of infection in animals, should be reduced and eventually eliminated. Improved hygiene practices and controlled use of antibiotics in agriculture, animal husbandry, and fisheries are desirable for environmental management and public health protection.